Effect of cold atmospheric plasma and pulsed electromagnetic fields on strawberry quality and shelf-life. (March 2021) - Giannoglou, Marianna; Xanthou, Zacharoula-Maria; Chanioti, Sofia; Stergiou, Panagiota; Christopoulos, Miltiadis; Dimitrakellis, Panagiotis; Efthimiadou, Αspasia; Gogolides, Εvangelos; Katsaros, George
Abstract: The effect of cold atmospheric plasma (CAP) and pulsed electromagnetic fields (PEMF) on the metabolic process, microbiological, enzymatic and quality parameters of fresh strawberries, after processing and during storage at 1 and 6 °C, was studied. CAP was more effective on microorganisms, reducing the total viable count by ~0.9 logCFU/g. Phenolic compounds and antioxidant activity were increased after CAP processing by ~20.9 and 16.5%, respectively. PEMF strawberries were firmless by ~16% compared to control. Both treatments did not significantly affect the weight loss, color, anthocyanins content and pH-value. B-glucosidase activity was higher for PEMF strawberries by at least 35 and 20%, compared to control and CAP respectively, explaining PEMF enhancing aromatic-profile. Ascorbic acid was decreased during storage, nevertheless, nonthermal treated samples showed higher values by at least 10%, compared to control samples. The shelf-life at 1 °C for control, CAP and PEMF strawberries was estimated as 13, 17 and 15 days, respectively. Graphical abstract: Unlabelled Image Highlights: Cold atmospheric plasma (CAP) reduced initial microbial load by 0.9 logCFU/g. CAP increased phenolic compounds and antioxidant activity by 20.9 and 16.5%. Pulsed electromagnetic fields (PEMF) treated strawberries were firmless by 16%. Shelf-life estimated as 13, 17 and 15 days at 1 °C for control, CAP and PEMF strawberries.